In Vitro Cytotoxic and Molecular Docking Studies of the Network Pharmacology Approach From Bioactive Compounds of Coleus amboinicus Leaves Against Lung and Breast Cancer Cells - Kasta Gurning; Gian Primahana; Endang Astuti; Winarto Haryadi (Advances in Pharmacological and Pharmaceutical Sciences)
Lung cancer and breast cancer are two types of cancer that cause and contribute to the highest mortality rate in the world. The development of anticancer agents that have high efficacy and relatively low side effects continues to be developed and is the focus of research, and one of the raw materials that can be explored is active compounds sourced from natural materials, one of which is plants. This study aims to isolate active compounds from bangun-bangun (Coleus amboinicus, Lour.) leaves, test cytotoxicity as an antilung and breast cancer agent in vitro, and conduct molecular docking studies with a network pharmacology approach on the pathways in cancer. Research methods include extraction by the maceration method and purification by column chromatography, anticancer activity testing is carried out by the microtetrazolium (MTT) test method against lung cancer (A549), breast cancer (MCF-7), and normal cells (CV-1), and molecular docking studies are carried out with a network pharmacology approach focused on proteins in cancer pathways. The results of the active isolate (InH-2) from n-hexane extract showed the best activity against lung cancer/A549 cells (IC50 31.74 μg/mL), and the active isolate (IEtOAc-1) from ethyl acetate extract showed the best activity against breast cancer/MCF-7 cells (IC50 80.05 μg/mL) and showed no toxicity to normal cells (CV-1). The results of the bioinformatic study are with a network pharmacology approach on the cancer pathway of bioactive compounds from each isolate target the matrix metalloproteinase-2 (MMP-2) protein. The content of bioactive compounds from Coleus amboinicus leaves shows the potential to be used as active agents in the treatment of lung cancer and breast cancer in the future.